2015
DOI: 10.3390/geriatrics1010002
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation on the Association between Depressive Symptoms and Driving Performance in Heart Failure

Abstract: Heart failure (HF) patients commit many errors on driving simulation tasks and cognitive dysfunction appears to be one important contributor to impaired driving in HF. Clinical modifiers of cognition may also play a key role. In particular, depression is common in HF patients, linked with cognitive dysfunction, and contributes to reduced driving fitness in non-HF samples. However, the associations among depressive symptoms, cognition, and driving in HF are unclear. Eighteen HF patients completed a validated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A power calculation based on previously published studies (19,20) found that a sample size of a total of 57 subjects (sum of patients and escorts) is required to demonstrate a difference of 3 midline traffic crossings, which we considered to represent a meaningful increase in the risk of accidents, with a power of 0.8 and an alpha of 0.05. Participants were recruited until complete data from 30 patients and 30 matched escorts were obtained.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…A power calculation based on previously published studies (19,20) found that a sample size of a total of 57 subjects (sum of patients and escorts) is required to demonstrate a difference of 3 midline traffic crossings, which we considered to represent a meaningful increase in the risk of accidents, with a power of 0.8 and an alpha of 0.05. Participants were recruited until complete data from 30 patients and 30 matched escorts were obtained.…”
Section: Sample Size Calculationmentioning
confidence: 99%